EFEKTIVITAS JUS BUAH PARE (Momordica charantia L) TERHADAP PENURUNAN KADAR TRIGLISERIDA PADA TIKUS GALUR WISTAR YANG DIINDUKSI PAKAN TINGGI LEMAK - SILALAHI, RINDI ARISKA; HARIAJI, ILHAM (JURNAL ILMIAH SIMANTEK, 2023)
Hyperlipidemia is often a cause of life-threatening cardiovascular disease. Pare fruit has antioxidants which are thought to have properties in reducing cholesterol levels. To determine the potential of bitter melon juice (Momordica charantia L.) in reducing triglyceride levels in Wistar rats induced by high-fat diet. The research method true Experiment with a pretest – posttest with control group design using 24 Wistar rats fed a high-fat diet and divided into 4 groups: negative control, positive control, group 1 (1.8 mL bitter melon juice) and group 2 (2.7 mL bitter gourd juice). The data analysis that will be used is the Paired T Test. The result of this research are triglyceride levels were found to significantly decrease with 1.8 mL of bitter melon juice (p<0.003) and 2.7 mL of bitter melon juice (p<0.001). Bitter gourd juice (Momordica charantia L.) is effective in reducing triglyceride levels in Wistar rats induced by high fat diet.